Classification and Identification of S Haplotypes in Radish Based on SRK Kinase Domain Sequence Analysis - Meng Ni; Xiaofang Yi; Qin Wang; Juan Wang; Shuang Wang; Liwang Liu; Liang Xu; Yan Wang (Plants, 2022)
Radish is a typical self-incompatible crop. The rapid and accurate identification of S haplotypes can circumvent the blindness of the hybrid combination process, which is critical in radish heterosis utilization and the breeding of new varieties. In this study, based on the gene sequence which encodes the S-locus receptor kinase (SRK) of radish, and the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis, the S haplotypes were identified among 79 cultivated radish genotypes. The PCR results indicated that 79 radish genotypes could be divided into 48 Class I, 13 Class II, and 17 Class I/II S haplotypes. Sequence alignment confirmed that the Class I materials contained 19 S haplotypes, of which three haplotypes (‘NAU-S53’, ‘NAU-S54’ and ‘NAU-S55’) were identified for the first time in radish. After digestion using the Hinf I restriction endonuclease, the SRK domain of DNA fragments of different genotypes showed high polymorphism. Homozygous materials S haplotypes could be quickly distinguished by the differences in the digested bands. Molecular identification of the S haplotype was highly consistent with the field pollination and pollen tube germination results. These results would provide an important approach for the rapid identification of radish S haplotypes and the efficient utilization of self-incompatibility in heterosis breeding.